Employee Work Competence Mediates the Impact of Work Experience on Employee Work Productivity (Stella Maris Hospital Study) - Laia, Ferima; Sari, Ade Indah; Setiamy, Arasy Ayu (Indonesian Journal of Advanced Research, 2026)
Human resource management is the science and art of managing worker relationships and functions so that they can effectively and efficiently contribute to the accomplishment of organizational, employee, and community goals. The degree to which a business meets its objectives determines whether it succeeds or fails. The availability of sufficient human resources at Stella Maris Hospital is one of the elements influencing a business's performance in reaching its objectives. The aim of this study was to investigate the effects of work experience and competence on Stella Marris Hospital employees' productivity.Path analysis was the research methodology adopted in this study. A sample of 92 Stella Marris Hospital employees was taken. The results of the study demonstrate how employees' productivity at Stella Maris Hospital is greatly influenced, either entirely or partially, by their level of competence and work experience.